Reclaiming the Colombian English Language Teaching Field to Sow the Seeds of Change Through Self-Study - Paula Pérez-Rubiano; Anna Peñaloza-Rallón; Julieth López-Acevedo; Sonia Camargo-Albarracín (Universidad Nacional de Colombia, 2024)
A growing interest in teacher identity and decision-making has emerged in language teaching; however, studies where English language teaching (ELT) educators reflect on their own practice are limited. We engaged in a self-study to understand how our experiences influenced our ELT educator identity at a public university in Colombia. A constructivist paradigm enabled us to focus on intra and interpersonal reflection as we created artifacts and met to discuss our teaching experiences. Using collaborative analysis, we developed our main themes represented by a red poppy. Based on the findings, our teaching identity is shaped by our families and teachers (roots), teaching misconceptions (leaves), new teaching experiences (new blossoms), other identities (petals), world views about education (cotton soul), and social justice agenda (seeds of change).